Two autolytic processing reactions of a satellite RNA proceed with inversion of configuration. - van Tol, H (1990)
Both polarities of the satellite RNA of tobacco ringspot virus occur in infected cells in multimeric forms which are capable of autolytic processing, using different sequences and structures [Feldstein, P.A., et al., Proc. Nat. Acad. Sci. USA (1990) 87 (in press)]. These transesterification reactions generate a 2',3'-cyclophosphate and a 5'-hydroxyl as the two new end groups. Cleavage is at a CpA for the (+) polarity RNA and at an ApG for the (-) polarity RNA. We enzymically synthesized oligoribonucleotides with processing capability and with specific 35S-labeled phosphorothioate diesters in the Rp configuration. After processing had occurred, the terminal nucleoside-2',3'-cyclophosphorothioate diester residues were recovered from the appropriate product by digestion with nuclease and phosphatase. Comparisons with specially prepared endo- and exoisomer reference compounds by thin layer chromatography and autoradiography revealed that the [35S]cytidine- and [35S]adenosine-2',3'-cyclophosphorothioate both were endo-isomers. The results are consistent with transesterification occurring by an inline SN2(P) attack of the 2'-hydroxyl group in the autolytic processing reactions of both polarities of the satellite RNA.